The Use Of Youtube As English Language Media To Improve Students Writing Skill In Procedute Text - Natanael Saragih; Rohdearni Wati Sipayung; Putri Arisa Dila Sinaga (Program Studi Pendidikan Bahasa Inggris FKIP, 2023)
The purpose of this study was to determine the application of YouTube videos to improve students' ability to write procedural texts and to determine students' perceptions of the application of YouTube videos. Data was collected by giving pre-test and post-test. The population of this study was 198 people and the research sample was students of class X OTKP SMK Prama Arta Bandar Huluan Private School year 2022/2023. The researcher took 1 class as a sample of class X OTKP SMK Prama Arta Bandar Huluan which consisted of 33 students. The sample was taken using saturated sampling. The results showed that the students' ability to write procedural texts using YouTube videos on the pre-test and post-test differed significantly. The t-test value is greater than the t-table. That is t-value (1.782) > t-table (1.756) and sig. (2-tailed) lower post test scores 0.000 <0.05. This shows that the alternative hypothesis (H1) is accepted and the null hypothesis (H0) is rejected. It can be concluded that the application of YouTube videos is effective in improving students' ability to write procedural texts. While the average score of students' perceptions of using YouTube videos was 81. This indicated that students gave very positive responses or agreed that YouTubevideos were useful and could improve their ability to write procedural texts